Strategi Dakwah Lembaga Gerakan Ahli Sedekah dalam Penanaman Kesadaran Bersedekah di Bandung - Alifa Nur Ramdhani (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Islam as a da'wah religion requires each of its adherents to preach according to their abilities, da'wah can be carried out by anyone, both individuals or the scale of people, such as institutions, organizations, communities, one of which is the Alms Expert Movement Institute. This institution preaches by inviting people to give alms, because da'wah does not have to be through lectures or tausyiah but can be in the form of simple things such as alms. The theory used in this research is the concept of strategy proposed by Fred R. David in Strategic Management Concepts. The concept through which there are three stages in the strategy process. The three stages are the strategy formulation stage, strategy implementation, and strategy evaluation stage. The research method used in this study is a qualitative descriptive research method, namely analyzing data based on information obtained from interviews, documentation studies and direct observations at the Institute for the Alms Expert Movement. Based on the results of the research conducted by the author, the da'wah strategy that has been carried out by the Alms Expert Movement goes through strategic stages consisting of strategy formulation in the form of determining the vision, mission and goals, environmental analysis, and planning program activities. and implementation strategies in the form of programs that raise funds, programs that distribute funds, and educational programs. as well as an evaluation strategy that evaluates the program as a whole and a pre-program evaluation that is carried out. Abstrak. Islam sebagai agama dakwah mewajibkan setiap pemeluknya untuk berdakwah sesuai dengan kemampuannya, dakwah dapat dilakukan oleh siapa saja baik perorangan atau skala orang banya seperti lembaga, organisasi, komunitas, salah satunya Lembaga Gerakan Ahli Sedekah. Lembaga ini berdakwah dengan mengajak masyarakat untuk bersedekah, karena dakwah tidak harus dengan ceramah atau tausyiah namun bisa berupa hal sederhana seperti sedekah. Teori yang digunakan dalam penelitian ini adalah konsep strategi yang dikemukakan oleh Fred R. David dalam Manajemen Strategis Konsep. Konsep yang dilalui terdapat tiga tahapan dalam proses strategi. Tiga tahapan tersebut adalah tahapan perumusan strategi, implementasi strategi, dan tahapan evaluasi strategi. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian deskriptif kualitatif yaitu menganalisis data berdasarkan informasi- informasi yang diperoleh dari hasil wawancara, studi dokumentasi dan observasi langsung pada Lembaga Gerakan Ahli Sedekah. Berdasarkan hasil penelitian yang dilakukan penulis, strategi dakwah yang telah dilakukan oleh Gerakan Ahli Sedekah melalui tahapan-tahapan strategi yang terdiri dari strategi perumusan berupa menentukan visi, misi dan tujuan, analisis lingkungan, dan perencanaan program kegiatan. dan strategi implementasi berupa program yang menggalang dana, program yang menyalurkan dana, dan program edukasi. serta strategi evaluasi yang mengevaluasi program secara menyeluruh dan evaluasi yang bersifat preprogram yang dilaksanakan.